Clinical Manifestations of Cardiac Disease in Patients with End Stage Renal Disease Under Maintenance Hemodialysis in a Tertiary Level Hospital of Nepal - Roka, Kumar; Roka, Pratibha Bista (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: End stage renal disease presents with multiple clinical and systemic manifestations. The aim of the present study was to identify the early cardiac and other morbidities in end stage renal disease (ESRD) patients who were under maintenance hemodialysis. Methods: This was an observational, prospective study conducted in fifty established ESRD patients of 20 to 74 years under maintenance hemodialysis in Nephrology unit of Shree Birendra Hospital. Clinical examination, laboratory parameters, electrocardiogram and echocardiography findings were used to identify the morbidities. Results: Among all patients enrolled in the study 88.7% had anemia, 64.2 % systolic murmurs, 62.26 % pedal edema, 73.6 % fatiguability, 71.7 % angina, 24.4 % palpitations and 13.2 % had breathlessness on exertion. 62.26% of the patients had hypertension and 13.20 % had diabetes. In the electrocardiogram, prolonged QTc was observed in 10.4%, followed by T wave inversion in 9.4 % and finally low voltage complex comprised 7.6 %. The echocardiogram showed left ventricular diastolic dysfunction in 58.5 %, left ventricular hypertrophy (overall type) 49 % and valvular lesion like mitral regurgitation and tricuspid regurgitation 83 % and 58.5 % respectively. Conclusion: Cardiac co-morbidities are common in patients diagnosed with ESRD on maintenance hemodialysis.